2010
DOI: 10.1002/ajh.21832
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of nitric oxide breathing in adult patients with sickle cell crisis

Abstract: In a cohort of children with sickle cell disease (SCD) and vaso-occlusive pain visits served through South Carolina's Medicaid system over a 6-year period (N 5 523), we compared the number of vaso-occlusive pain or acute chest syndrome (ACS)/pneumonia episodes, and outpatient or acute service costs in those treated or not treated with hydroxyurea (HU). HU may be an underused intervention for SCD in this practice setting, for a variety of reasons. Treatment with HU varied greatly, appears to have been administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 24 publications
2
39
1
2
Order By: Relevance
“…Despite positive early small phase II trials (53,54), we observed no effect of inhaled NO therapy on the duration of pain crisis, narcotic use, pain scores, or the development of ACS (18).…”
Section: Acs Treatmentmentioning
confidence: 63%
“…Despite positive early small phase II trials (53,54), we observed no effect of inhaled NO therapy on the duration of pain crisis, narcotic use, pain scores, or the development of ACS (18).…”
Section: Acs Treatmentmentioning
confidence: 63%
“…Our result showing a marked reduction in sRBC adhesion following NO breathing may be relevant to a physiological basis for the clinical improvements SCD patients experienced after NO inhalation during vaso-occlusive crisis 27 as well as to pain reduction. 28,29 Also, given that SCD patients with low NO metabolite levels experience higher levels of pain, 10 our results suggest that lower NO bioavailability increases the risk of vasoocclusive crisis under hypoxia. 26 Thus, the differences in the risk for cell adhesion might contribute to the clinical heterogeneity among SCD patients because sRBC adhesion is a crucial determinant for clinical severity.…”
Section: Discussionmentioning
confidence: 73%
“…NO inhalation for SCD patients under vaso-occlusive crisis reduced pain scores 28,29 ; however, another clinical trial was unable to reproduce the beneficial effects of NO inhalation. 34 Results from this study may suggest possible clues to the mechanisms underlying these conflicting results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The role of NO in erythrocyte function, sickle cell anemia, malaria, and damage to banked blood has been already reviewed, as well as the use of NO targeted therapies for erythrocyte disease (Maley et al, 2010). Pain from vaso-occlusive crisis is the major cause of hospitalization in patients with sickle cell disease, where beneficial therapeutic effects of inhaled NO have been demonstrated (Head et al, 2010). Decreased exhaled nitric oxide levels (FE NO ) have been described in patients with sickle cell disease, together with deficiency in plasma arginine.…”
Section: Nitric Oxide-related Therapy In Hemoglobinopathiesmentioning
confidence: 99%